A kind of wear-resistant floor concrete and preparation method thereof
By improving the shape of the machined sand particles and combining specific additives to form a skeleton compact structure, the problems of easy cracking and poor surface performance of wear-resistant floor concrete are solved, and high density, low shrinkage and good wear resistance are achieved.
Patent Information
- Application Number
- CN202311010012.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-11
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-08-11
AI Technical Summary
Existing wear-resistant floor concrete is prone to cracking after use for a period of time, affecting the aesthetics and durability. At the same time, concrete made of machine sand has poor ease, large slump loss, large shrinkage, and poor surface finish and wear resistance.
By improving the shape of the machine sand particles, combining lithium slag powder, magnesium fluorosilicate, aluminum dihydrogen phosphate, hydroxyapatite and nano calcium sulfate, a skeleton compact structure is formed, improving the compactness, wear resistance and crack resistance of concrete, while reducing shrinkage.
The obtained products have good compactness, low shrinkage properties, wear resistance and crack resistance, good working properties, strong water retention ability, high surface flatness, and are suitable for large-area floor construction.
Smart Images

Figure CN117069449B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and particularly relates to a wear-resistant floor concrete and a preparation method thereof. Background Art
[0002] Wear-resistant flooring is in great demand in industrial floors and places with high environmental requirements. It must have the characteristics of anti-corrosion, wear resistance, anti-skid, low pollution and strong decorative effect. Generally, wear-resistant concrete needs to be prepared with natural river sand. However, with the depletion of natural sand resources, concrete sand generally uses machine-made sand. However, the use of machine-made sand to prepare large-area floor concrete has obvious defects: poor workability, large slump loss, large shrinkage, poor surface finish and wear resistance, etc. At the same time, due to the large area and strong overall constraints of concrete floors, cracking is easy to occur after a period of use, which seriously affects the appearance and durability of concrete floors. Summary of the invention
[0003] The purpose of the present invention is to provide a wear-resistant floor concrete and a preparation method thereof. On the one hand, the particle shape of machine-made sand is improved and the matching effect between aggregates is fully utilized to form a skeleton density structure; on the other hand, the density, wear resistance and crack resistance of the concrete are improved while the shrinkage is reduced by introducing lithium slag powder, magnesium fluorosilicate, aluminum dihydrogen phosphate, hydroxyapatite and nano calcium sulfate; the obtained product has good workability, strong water retention capacity, strong surface wear resistance and strong crack resistance.
[0004] In order to achieve the above purpose, the technical solutions adopted are as follows:
[0005] A wear-resistant floor concrete, which is composed of cement 250-300kg / m 3 , lithium slag powder 50~100kg / m 3 , magnesium fluorosilicate 1~3kg / m 3 , aluminum dihydrogen phosphate 0.5~2kg / m 3 , hydroxyapatite 0.5~5kg / m 3 , nano calcium sulfate 0.5~1kg / m 3 , crushed stone 1200~1400kg / m 3 , machine-made sand 700~900kg / m 3 , water reducing agent 5~10kg / m 3 , water 140~170kg / m 3 .
[0006] According to the above scheme, the cement is ordinary Portland cement or silicate cement, the strength grade of which is not less than 42.5, and the performance meets the requirements of "General Portland Cement" GB 175-2007.
[0007] According to the above scheme, the lithium slag powder is a powder material discarded after lithium is extracted from spodumene ore; its composition is SiO2 content 20% to 40%, Al2O3 content 15% to 25%, SO3 content 15%-20%, CaO content 10% to 20%, and the remaining components are not more than 1%; the specific surface area is not less than 400m 2 / kg, 28d activity index is not less than 95%, and other properties meet the requirements of "Lithium slag powder used in cement and concrete" YB / T4230-2010.
[0008] According to the above scheme, the magnesium fluorosilicate is a white crystalline powder with a free water content of no more than 1% and a relative density of 1.788.
[0009] According to the above scheme, the aluminum dihydrogen phosphate is a colorless and odorless white powder with a relative density of 1.44 to 1.47.
[0010] According to the above scheme, the hydroxyapatite is a porous powder with a melting point of 1600°C to 1700°C and a specific gravity of 3.10 to 3.20 g / cm 3 , solubility is 0.3~0.5ppm, Ca / P is 1.67.
[0011] According to the above scheme, the CaSO4 content of the nano calcium sulfate is ≥98%, the melting point is 1400℃~1500℃, the water solubility (22℃) is <1200ppm, and the density is 2.65ɡ / cm 3 ~2.70ɡ / cm 3 , particle size is 30-50nm and aspect ratio is 10-20.
[0012] According to the above scheme, the crushed stone is 5mm~31.5mm continuously graded crushed stone, the mass content of 19.0mm~31.5mm particles is not less than 50%, the void ratio is not more than 40%, and the other properties meet the requirements of "Crushed Stone and Pebbles for Construction" GB / T 14685-2011.
[0013] According to the above scheme, the machine-made sand belongs to the medium sand of zone II, with a fineness modulus of 2.6-2.8, particles below 0.15 mm not exceeding 5%, and an average roundness of the processed particles not less than 0.95.
[0014] According to the above scheme, the water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is not less than 25%.
[0015] The preparation method of the above-mentioned wear-resistant floor concrete comprises the following steps:
[0016] Put lithium slag powder, magnesium fluorosilicate, aluminum dihydrogen phosphate, hydroxyapatite and nano calcium sulfate into a mixer and grind them for 5 to 10 minutes to form a mixture; put crushed stone, cement, the mixture, machine-made sand, water and water reducing agent into the mixer in turn and stir for 2 to 5 minutes to obtain wear-resistant floor concrete.
[0017] The lithium slag powder used in the present invention contains more active Al2O3, SiO2 and SO3, which can react with cement paste and play a "filling role" of micro-aggregate. At the same time, as the concrete reacts, the temperature inside the concrete can reach 40℃~70℃. At a certain temperature, SO3 in the lithium slag powder and Ca in the cement paste 2+ Calcium sulfate can be formed in an alkaline environment. The dissolved calcium sulfate will precipitate continuously as the concrete is hardened, squeezed and the temperature decreases. Under the guidance of nano-calcium sulfate crystal nuclei, it will continue to grow to form calcium sulfate whiskers, which can reduce the shrinkage of concrete and improve the concrete's resistance to cracking, wear resistance and stability.
[0018] Nano calcium sulfate in fresh concrete will make cement paste more delicate and easy to flow, thus improving the fluidity and density of concrete. With the chemical reaction inside the concrete, nano calcium sulfate also plays the role of crystal nucleus. Its suitable aspect ratio can guide the generated and precipitated calcium sulfate to grow continuously at both ends, eventually forming calcium sulfate whiskers.
[0019] When magnesium fluorosilicate is added in low amounts, its hydrolysis products react chemically with calcium hydroxide, a cement hydration product, to generate certain crystalline substances, which cover the surface of the cement hydration product and then prevent the migration of the hydration reaction, thereby playing a retarding role, extending the setting time of cement, increasing the fluidity of mortar and the slump of concrete, and at the same time reacting with alkali to form fluoride and silica to fill pores, etc., which can increase the early and late compressive strength of concrete to a certain extent.
[0020] Aluminum dihydrogen phosphate has a certain retarding effect on cement, and can react with calcium hydroxide in cement slurry to form insoluble tricalcium phosphate precipitate, which continuously fills the capillary pores and microcracks of concrete during the hydration process, tightly wraps the calcium sulfate whiskers, improves the bonding performance, and thus enhances the hardness, impermeability and durability of concrete.
[0021] Hydroxyapatite is a soluble organic calcium that can form hydrogen bonds and van der Waals forces with calcium sulfate molecules, thereby temporarily increasing the solubility of the generated calcium sulfate in the early stage of concrete hydration, making it easier for calcium sulfate to be slowly released and precipitated after the concrete has hydrated to a certain degree, and making it easier for calcium sulfate whiskers to gradually grow mainly along the longitudinal direction. In the later stage of concrete hydration, the concrete becomes more and more alkaline, and hydroxyapatite becomes slightly soluble and has a certain spatial induction ability, which promotes the dispersion of the generated calcium sulfate whiskers and presents a spatial skeleton distribution, enhancing the improvement of concrete strength, shrinkage crack resistance and wear resistance by calcium sulfate whiskers. In addition, it has a porous structure inside, which can absorb and store a certain amount of water, so that the concrete water is slowly released, avoiding cracking caused by excessive surface water loss.
[0022] In the process of the present invention, cement is used as the main gelling material, the sulfur source provided by the lithium slag powder and the Ca in the cement slurry 2+ In an alkaline environment, calcium sulfate whiskers are continuously grown with nano-calcium sulfate as the crystal nucleus. The slow setting effect of low-doped magnesium fluorosilicate and aluminum dihydrogen phosphate allows the length of nano-calcium sulfate to reach hundreds of microns or even above the millimeter level after growth. In addition, aluminum dihydrogen phosphate reacts with Ca(OH)2 in the cement slurry to form insoluble tricalcium phosphate precipitates, and magnesium fluorosilicate reacts with Ca(OH)2 in the cement slurry to form fluoride and silicon dioxide, which continuously fill the capillaries and microcracks of the concrete and enhance the bond strength between the calcium sulfate whiskers and the slurry. Hydroxyapatite can form hydrogen bonds and van der Waals forces with calcium sulfate molecules, causing the precipitated calcium sulfate whiskers to grow and elongate mainly along the longitudinal direction, and can cause the calcium sulfate whiskers to disperse and present a spatial skeleton-like distribution, enhancing the homogeneity and isotropic properties of the calcium sulfate whiskers in concrete. The generated calcium sulfate whiskers in concrete play a reinforcing role, which can improve the toughness of concrete, increase the flexural resistance of concrete, inhibit the shrinkage of concrete, effectively control the cracking of concrete, increase the compressive strength of concrete appropriately, and improve the wear resistance and stability of concrete floors.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. Compared with ordinary concrete of the same strength grade, the wear-resistant concrete of the present invention has better compactness, low shrinkage performance, better wear resistance and crack resistance, and its workability and compressive strength are also improved.
[0025] 2. Using industrial waste lithium slag as a concrete admixture in wear-resistant concrete can achieve high added value utilization of lithium slag, broaden the scope of use of lithium slag, reduce cement consumption, save costs and energy resources, and be beneficial to the protection of the ecological environment and the resource utilization of industrial waste.
[0026] 3. Using artificial sand instead of natural sand in wear-resistant floors can reduce dependence on natural sand resources and reduce damage to the natural environment.
[0027] 4. The wear-resistant floor concrete prepared by the present invention has the advantages of good workability, strong water retention capacity, small shrinkage, strong crack resistance, good surface flatness, good wear resistance, etc. At the same time, the construction operability is greatly improved and can be widely promoted and applied. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 : Shrinkage deformation rate of the wear-resistant concrete obtained in Examples 1-8. DETAILED DESCRIPTION
[0029] The following examples further illustrate the technical solution of the present invention, but are not intended to limit the scope of protection of the present invention.
[0030] The specific implementation method provides a wear-resistant floor concrete, which is composed of cement 250-300 kg / m 3 , lithium slag powder 50~100kg / m 3 , magnesium fluorosilicate 1~3kg / m 3 , aluminum dihydrogen phosphate 0.5~2kg / m 3 , hydroxyapatite 0.5~5kg / m 3 , nano calcium sulfate 0.5~1kg / m 3 , crushed stone 1200~1400kg / m 3 , machine-made sand 700~900kg / m 3 , water reducing agent 5~10kg / m 3 , water 140~170kg / m 3 .
[0031] Specifically, the cement is ordinary Portland cement or silicate cement, the strength grade of which is not less than 42.5, and the performance of which meets the requirements of "General Portland Cement" GB 175-2007.
[0032] Specifically, the lithium slag powder is a powder material discarded after lithium is extracted from spodumene ore; its composition is SiO2 content 20% to 40%, Al2O3 content 15% to 25%, SO3 content 15%-20%, CaO content 10% to 20%, and the remaining components are not more than 1%; the specific surface area is not less than 400m 2 / kg, 28d activity index is not less than 95%, and other properties meet the requirements of "Lithium slag powder used in cement and concrete" YB / T4230-2010.
[0033] Specifically, the magnesium fluorosilicate is a white crystalline powder with a free water content of no more than 1% and a relative density of 1.788.
[0034] Specifically, the aluminum dihydrogen phosphate is a colorless and odorless white powder with a relative density of 1.44 to 1.47.
[0035] Specifically, the hydroxyapatite is a porous powder with a melting point of 1600°C to 1700°C and a specific gravity of 3.10 to 3.20 g / cm 3 , solubility is 0.3~0.5ppm, Ca / P is 1.67.
[0036] Specifically, the nano calcium sulfate has a CaSO4 content of ≥98%, a melting point of 1400°C to 1500°C, a water solubility (22°C) of <1200ppm, and a density of 2.65ɡ / cm 3 ~2.70ɡ / cm 3 , particle size is 30-50nm and aspect ratio is 10-20.
[0037] Specifically, the crushed stone is 5mm-31.5mm continuously graded crushed stone, the mass content of 19.0mm-31.5mm particles is not less than 50%, the void ratio is not more than 40%, and the other properties meet the requirements of "Crushed Stone and Pebbles for Construction" GB / T 14685-2011.
[0038] Specifically, the machine-made sand belongs to zone II medium sand, has a fineness modulus of 2.6 to 2.8, has particles below 0.15 mm not exceeding 5%, and has an average roundness of not less than 0.95 after processing.
[0039] According to the above scheme, the water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is not less than 25%.
[0040] The specific implementation also provides a method for preparing the above-mentioned wear-resistant floor concrete, comprising the following steps:
[0041] Put lithium slag powder, magnesium fluorosilicate, aluminum dihydrogen phosphate, hydroxyapatite and nano calcium sulfate into a mixer and grind them for 5 to 10 minutes to form a mixture; put crushed stone, cement, the mixture, machine-made sand, water and water reducing agent into the mixer in turn and stir for 2 to 5 minutes to obtain wear-resistant floor concrete.
[0042] The physical and chemical properties of the technical solution of the present invention are compared with ordinary concrete and concrete added with an expansive agent. When the total amount of cementitious materials in the concrete remains unchanged, the mineral admixture of the blank group adopts Class I fly ash. Generally speaking, Class I fly ash also has a relatively obvious improvement on the shrinkage of concrete. The expansive agent adopts CSA expansive agent, and the internal admixture method is adopted. Its expansion performance is mainly based on the generation of calcium aluminate. The amount of powder, machine-made sand, crushed stone, water reducer and water in the concrete is kept fixed. The specific mix ratio of the benchmark mix ratio is shown in Table 1, wherein No. 1 to 4 are blank groups, and No. 5 to 8 are control groups.
[0043] Table 1 Experimental Examples 1-8 Benchmark Concrete Mix Information (kg / m 3 )
[0044]
[0045]
[0046] The above experimental examples 1-8 were all tested and verified using a twin-shaft forced stirring pot with a maximum single stirring volume of 80L. The trial mixing steps are as follows: (1) accurately weigh 60L of materials required for trial mixing, control the error of aggregate to be less than ±1.0%, the error of powder to be less than ±0.5%, and the error of liquid to be less than ±0.2%; (2) successively put crushed stone, mixed material, cement, machine-made sand, water and admixture into a mixer and stir for 2min to 5min before taking out of the mixer to form a wear-resistant floor concrete; (3) stir evenly with a shovel after taking out of the mixer, test the slump and expansion of the concrete mixture, and retain 7d and 28d cubic compression test blocks respectively. Refer to the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" GBT50082-2009 to test the length change value of concrete from the time it is out of the pot to the age of 3d using a non-contact shrinkage hardness tester (positive for expansion, negative for contraction), use a flat plate shrinkage cracking device to test the cracking condition of concrete after 3d age, and the wear resistance test method is carried out in accordance with JTJ053-94. The concrete mechanical properties and plate shrinkage cracking of each experimental example are shown in Table 2. The concrete deformation test values are shown in Figure 1 shown.
[0047] Table 2 Basic properties of trial mixed concrete in Examples 1-8
[0048]
[0049] As can be seen from Table 2 above, compared with Example 1, and compared with Example 2, the strength of the concrete after adding CSA expansion agent in Example 2 is slightly greater than that of the embodiment without expansion agent, and the 3d flat plate cracking condition is significantly better than that of the concrete without expansion agent. This is because the expansion agent can improve the density of concrete and reduce the shrinkage of concrete to a certain extent. The strength of concrete added with lithium slag is higher than that of concrete added with Class I fly ash, but the workability is poor, because lithium slag itself has a porous structure that can absorb water, resulting in poor workability. At the same time, lithium slag has a large specific surface area and contains more active substances, which can improve the strength of concrete to a certain extent. Embodiment 5 / 6 / 7 / 8 is the present invention. It can be seen from Table 2 that its 28d strength and strength growth rate are significantly better than those of Embodiment 1 / 2 / 3 / 4, that is, the present invention has a significant effect on improving the strength of concrete; at the same time, the wear amount is also significantly less than that of Embodiment 1 / 2 / 3 / 4, that is, the concrete of the present invention has good wear resistance, and the total area of slab cracking is also significantly less than that of Embodiment 1 / 3, and slightly less than that of Embodiment 2 / 4 with the addition of the expansion agent CSA, which can reduce the cracking phenomenon of large-area concrete floor construction.
[0050] from Figure 1 It can be seen that the shrinkage of Example 2 / 4 after adding the expansion agent to the concrete is less than that of Example 1 / 3. This is because the expansion agent can produce an expansion effect to compensate for a certain amount of concrete shrinkage. The shrinkage of Examples 5 / 6 / 7 / 8 of the present invention is significantly better than that of Example 1 / 3, and even better than that of Example 2 / 4 of the concrete added with the CSA expansion agent. The slope of the shrinkage rate curve of Examples 5 / 6 / 7 / 8 is slower than that of Examples 1 / 2 / 3 / 4. Combined with Table 2, it can be seen that the present invention has a significant effect on the shrinkage and cracking of concrete, and can reduce the shrinkage and cracking phenomenon of concrete floors.
[0051] In summary, the present invention is beneficial to the working performance of concrete, can improve the strength of concrete, has good compactness, low shrinkage performance, good wear resistance and crack resistance, and the use of machine-made sand as raw material expands the scope of application of the present invention, which has good economic and social benefits.
Claims
1. A wear-resistant floor concrete, characterized in that Composition: cement 250~300kg / m 3 , lithium slag powder 50~100kg / m 3 , magnesium fluorosilicate 1~3kg / m 3 , aluminum dihydrogen phosphate 0.5~2kg / m 3 , hydroxyapatite 0.5~5kg / m 3 , nano calcium sulfate 0.5~1kg / m 3 , crushed stone 1200~1400kg / m 3 , machine-made sand 700~900kg / m 3 , water reducing agent 5~10kg / m 3 , water 140~170kg / m 3 ; The lithium slag powder is a powder material discarded after lithium is extracted from spodumene ore; its composition is SiO2 content 20%~40%, Al2O3 content 15%~25%, SO3 content 15%-20%, CaO content 10%~20%, and the remaining components are not more than 1%; the specific surface area is not less than 400m 2 / kg, 28d activity index is not less than 95%, and other properties meet the requirements of "Lithium slag powder used in cement and concrete" YB / T4230-2010.
2. The wear-resistant floor concrete according to claim 1, characterized in that The cement is ordinary Portland cement or silicate cement, with a strength grade of not less than 42.5 and performance meeting the requirements of "General Portland Cement" GB 175-2007.
3. The wear-resistant floor concrete according to claim 1, characterized in that The magnesium fluorosilicate is a white crystalline powder with a free water content of no more than 1% and a relative density of 1.
788.
4. The wear-resistant floor concrete according to claim 1, characterized in that The aluminum dihydrogen phosphate is a colorless and odorless white powder with a relative density of 1.44 to 1.
47.
5. The wear-resistant floor concrete according to claim 1, characterized in that The hydroxyapatite is a porous powder with a melting point of 1600°C to 1700°C and a specific gravity of 3.10 to 3.20 g / cm 3 , solubility is 0.3~0.5ppm, Ca / P is 1.
67.
6. The wear-resistant floor concrete according to claim 1, characterized in that The nano calcium sulfate has a CaSO4 content of ≥98%, a melting point of 1400°C to 1500°C, a water solubility of <1200ppm at 22°C, and a density of 2.65ɡ / cm 3 ~2.70ɡ / cm 3 , particle size is 30-50nm and aspect ratio is 10-20.
7. The wear-resistant floor concrete according to claim 1, characterized in that The crushed stone is 5mm~31.5mm continuously graded crushed stone, the mass content of 19.0mm~31.5mm particles is not less than 50%, the void ratio is not more than 40%, and the other properties meet the requirements of "Crushed Stone and Pebbles for Construction" GB / T 14685-2011.
8. The wear-resistant floor concrete according to claim 1, characterized in that The machine-made sand belongs to the medium sand in Zone II, with a fineness modulus of 2.6~2.8, particles below 0.15 mm not exceeding 5%, and an average roundness of particles after treatment not less than 0.
95.
9. The method for preparing the wear-resistant floor concrete according to claim 1, characterized in that The following steps are involved: Put lithium slag powder, magnesium fluorosilicate, aluminum dihydrogen phosphate, hydroxyapatite and nano calcium sulfate into a mixer and grind them for 5 to 10 minutes to form a mixture; put crushed stone, cement, the mixture, machine-made sand, water and water reducing agent into the mixer in turn and stir for 2 to 5 minutes to obtain wear-resistant floor concrete.
Citation Information
Patent Citations
High-strength self-compacting concrete and preparation method thereof
CN111410489A
Lithium slag modified ultra-high performance concrete product and preparation method thereof
CN111848029A
Cited By
Ecological concrete and preparation method thereof
CN121494420A